2014
DOI: 10.1073/pnas.1411723111
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial network organization imprints on microbial co-occurrence networks

Abstract: Recent studies highlight linkages among the architecture of ecological networks, their persistence facing environmental disturbance, and the related patterns of biodiversity. A hitherto unresolved question is whether the structure of the landscape inhabited by organisms leaves an imprint on their ecological networks. We analyzed, based on pyrosequencing profiling of the biofilm communities in 114 streams, how features inherent to fluvial networks affect the co-occurrence networks that the microorganisms form i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(160 citation statements)
references
References 44 publications
5
155
0
Order By: Relevance
“…This notion is supported by the observation that, under elevated flow velocity, Flavobacteriia adhere better to surfaces than Pseudomonas aeruginosa, which is a notable biofilm former 30 . Furthermore, analyses of co-occurrence networks identified Sphingobacteriia as a key taxonomic group in stream biofilms 31 , which agrees with the involvement of these bacteria in the formation and colonization of suspended aggregates in the ocean and lakes 29 . Other bacteria that are commonly found in stream biofilms, but at lower relative abundance, include Gammaproteobacteria, Deltaproteobacteria, Actinobacteria, Firmicutes, Gemmatimonadetes, Verrucomicrobia, Planctomycetes and DeinococcusThermus.…”
Section: Biodiversity Across Spatial Scalessupporting
confidence: 75%
See 1 more Smart Citation
“…This notion is supported by the observation that, under elevated flow velocity, Flavobacteriia adhere better to surfaces than Pseudomonas aeruginosa, which is a notable biofilm former 30 . Furthermore, analyses of co-occurrence networks identified Sphingobacteriia as a key taxonomic group in stream biofilms 31 , which agrees with the involvement of these bacteria in the formation and colonization of suspended aggregates in the ocean and lakes 29 . Other bacteria that are commonly found in stream biofilms, but at lower relative abundance, include Gammaproteobacteria, Deltaproteobacteria, Actinobacteria, Firmicutes, Gemmatimonadetes, Verrucomicrobia, Planctomycetes and DeinococcusThermus.…”
Section: Biodiversity Across Spatial Scalessupporting
confidence: 75%
“…Analyses of co-occurrence networks generated from 16S rRNA sequencing data showed that community networks tend to fragment into more abundant, but smaller, clusters that may be sensitive to the hydrological regime and dispersal dynamics 31 . The same study also uncovered the role of typical biofilm formers, such as Sphingobacteriia, in the organization of biofilm community networks.…”
mentioning
confidence: 99%
“…In fact, dispersal limitation is commonly believed to be higher in the headwater reaches (Besemer et al, 2013), which would induce stronger constraints on the colonisation dynamics of microbial specialists. Furthermore, the combination of elevated physical disturbance (e.g., hydrology) on microbial communities (Widder et al, 2014) upstream with the observation that postdisturbance recovery of specialists is less successful than for generalists (Clavel et al, 2011) may further contribute to the spatial patterns of functional traits we observed in this study. Finally, benthic algae which provide the bulk DOC source in streams above the treeline exude compounds, often monomeric in nature, that do not require specialised metabolic pathways and that are therefore readily available to a wide range of microbial heterotrophs (Kaplan and Bott, 1989).…”
Section: Discussionmentioning
confidence: 65%
“…Confluences are important ecological elements for a number of other reasons too and there is broad recognition amongst ecologists that understanding confluence, link and networks effects is essential for improving understanding of the spatial and temporal distribution of river organisms and the collective health of river ecosystems (Davey and Lapointe, 2007;Poole 2002;Benda et al, 2004b;Thorp et al, 2006;Grant et al, 2007;Widder et al, 2014;Thorp, 2014;Erös and Grant, 2015;Lanthier et al 2015;Hauer 2015). The simple relations identified here, between the frequency and likelihood of tributary-driven aggradation and basin shape and size, support Benda's Network Dynamics Hypothesis (Benda et al, 2004b) In turn, to the extent that physical heterogeneity matters for biodiversity and ecosystem health, the cumulative ecological benefit of tributary-driven aggradation should be greater in more compact basins; a hypothesis that remains to be tested.…”
Section: Discussionmentioning
confidence: 99%